2020
DOI: 10.2807/1560-7917.es.2020.25.44.1900420
|View full text |Cite
|
Sign up to set email alerts
|

Do point-of-care tests (POCTs) offer a new paradigm for the management of patients with influenza?

Abstract: Jim. Do pointof-care tests (POCTs) offer a new paradigm for the management of patients with influenza?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…This is despite low influenza activity in the last two seasons due to the COVID‐19 pandemic. In Europe, a similar picture of lack of influenza A subtyping for laboratory confirmed cases in ICU can be seen in this current influenza season 10 …”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This is despite low influenza activity in the last two seasons due to the COVID‐19 pandemic. In Europe, a similar picture of lack of influenza A subtyping for laboratory confirmed cases in ICU can be seen in this current influenza season 10 …”
Section: Discussionsupporting
confidence: 66%
“…In Europe, a similar picture of lack of influenza A subtyping for laboratory confirmed cases in ICU can be seen in this current influenza season. 10 The survey also highlighted that when rapid influenza testing was used, just over half of the tests used did not subtype the influenza A positive samples and few of these samples were referred for any follow-up testing or confirmation. Of those samples that were referred for follow-up testing, it is unknown to what extent confirmatory results were received back and whether hospital Laboratory Information Management Systems (LIMS) were updated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…no drop in the percentage of positive tests), we propose the utilisation of POC results in the routine surveillance of seasonal influenza. A few authors have already suggested that seasonal response can improve with real-time monitoring via POC testing [24][25][26]. Also, de Lusignan et al inquired if POC testing could have a place at the level of general practices for influenzalike illness and influenza surveillance purposes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a perspective paper by Dickson et al [ 8 ] highlights the opportunities and challenges that influenza POCT presents, and describes potential solutions. Challenges highlighted by the authors include integration into clinical workflow, standardisation of protocols, data procurement for surveillance purposes, and characterisation of viral isolates.…”
mentioning
confidence: 99%